Antagonistic Effects of Ocean Acidification and Rising Sea Surface Temperature on the Dissolution of Coral Reef Carbonate Sediments - Trnovsky, Daniel; Stoltenberg, Laura; Cyronak, Tyler; Eyre, Bradley D. (Frontiers in Marine Science, 2016)
Increasing atmospheric CO2 is raising sea surface temperature (SST) and increasing seawater CO2 concentrations, resulting in a lower oceanic pH (ocean acidification; OA), which is expected to reduce the accretion of coral reef ecosystems. Although sediments comprise most of the calcium carbonate (CaCO3) within coral reefs, no in situ studies have looked at the combined effects of increased SST and OA on the dissolution of coral reef CaCO3 sediments. In situ benthic chamber incubations were used to measure dissolution rates in permeable CaCO3 sands under future OA and SST scenarios in a coral reef lagoon on Australia’s Great Barrier Reef (Heron Island). End of century (2100) simulations (temperature +2.7°C and pH -0.3) shifted carbonate sediments from net precipitating to net dissolving. Warming increased the rate of benthic respiration (R) by 29% per 1°C and lowered the ratio of productivity to respiration (P/R; ΔP/R = -0.23), which increased the rate of CaCO3 sediment dissolution (average net increase of 18.9 mmol CaCO3 m-2 d-1 for business as usual scenarios). This is most likely due to the influence of warming on benthic P/R which, in turn, was an important control on sediment dissolution through the respiratory production of CO2. The effect of increasing CO2 on CaCO3 sediment dissolution (average net increase of 6.5 mmol CaCO3 m-2 d-1 for business as usual scenarios) was significantly less than the effect of warming. However, the combined effect of increasing both SST and pCO2 on CaCO3 sediment dissolution was non-additive (average net increase of 5.6 mmol CaCO3 m-2 d-1) due to the different responses of the benthic community. This study highlights that benthic biogeochemical processes such as metabolism and associated CaCO3 sediment dissolution respond rapidly to changes in SST and OA, and that the response to multiple environmental changes are not necessarily additive.